Mucinous adenocarcinoma of the intestinal type arising from mature cystic teratoma of the ovary: a rare case report and review of the literature - Takai Masaaki; Kanemura Masanori; Kawaguchi Hiroshi; Fujiwara Satoe; Yoo Saha; Tanaka Yoshimichi; Tsunetoh Satoshi; Terai Yoshito; Yamada Takashi; Ohmichi Masahide (BMC, 2012)
Abstract Background Mature cystic teratomas (MCTs) are the most common germ cell tumors of the ovary. Malignant tranformation occurs in 1-2% of these neoplasms. Although most of the malignancies arising from MCTs are squamous cell carcinomas, adenocarcinoma of the gastrointestinal type is extremery rare. We herein present a case of adenocarcinoma of the intestinal type arising from a MCT. Case A 49-year-old female underwent surgery for a left ovarian tumor. The histology of the cyst walls revealed a MCT with a few hair shafts and a squamous layer, while another part of the tumor showed adenocarcinoma of the intestinal type. Five years after surgery, she is alive without disease.